Improved depiction of Indian summer monsoon in latest high resolution NCEP climate forecast system reanalysis. (6th November 2014) - Chaudhari, Hemantkumar S.; Pokhrel, Samir; Saha, Subodh K.; Dhakate, Ashish; Hazra, Anupam
ABSTRACT The improvements in representing the Indian summer monsoon features are assessed using the latest coupled global reanalysis, the climate forecast system reanalysis (CFSR) from National Centre for Environmental Predictions (NCEP) with respect to widely used NCEP‐reanalysis 2 (NCEP2). To validate the reanalysis product corresponding observations are also used. CFSR is more realistic in terms of spatial pattern of seasonal mean rainfall, first and second empirical orthogonal function (EOF) modes of interannual variability as compared with NCEP2 reanalysis. Percentage of total variance was explained by northward and westward propagating intraseasonal oscillation modes in CFSR that are better captured than those from NCEP2 reanalysis. Northward propagating mode is well depicted in CFSR as compared with that of NCEP2 and may be attributed to the strong vertical shear of zonal wind and strong meridional gradient of specific humidity in CFSR. Distribution of the north–south and east–west spectra of CFSR suggests much better conformity with observation as compared with NCEP2. Surface wind patterns of CFSR are having relatively small errors compared to Quick Scatterometer (QuikSCAT) winds. CFSR has some success in simulating observed sea surface temperature (SST)–rainfall relationship as well as in depicting the coupled ocean‐atmosphere phenomena of El Niño and Southern Oscillation (ENSO) in terms of Indian summer monsoon rainfall (ISMR) teleconnections. Overall monsoon features in CFSR are much closer to the observation as compared with NCEP2, and these may be because of the realistic representation of ocean–atmosphere feedback owing to the coupled model‐based reanalysis. This study will help in establishing the credibility of the CFSR in terms of realistic representation of Indian summer monsoon as compared with widely used atmospheric only reanalysis.